Islamic Law and State Confiscation of Illegitimately Acquired Wealth: A Case Study on the Ibadi Concept of Taghrīq - Mahmood Said Al Awaidi; Anke Iman Bouzenita (Mazahib, 2026)
This paper examines both the concept and application of taghrīq (state confiscation of illegitimately acquired wealth) in Ibāḍī Islamic jurisprudence, addressing a gap in scholarship on Islamic public financial law. It situates the concept within Islam’s prohibition of unlawful enrichment and explores how justice may be restored when restitution to rightful owners is impossible. The study reveals that taghrīq is a distinct Ibāḍī legal mechanism for addressing structural economic injustice, especially under illegitimate or oppressive rule. Methodologically, it combines doctrinal analysis of Ibāḍī legal texts with historical case studies from Oman, clarifying key concepts such as ghaṣb, Bayt al-māl, and jabbār, and examining precedents from early Islamic governance. It also outlines the legal conditions and scholarly debates governing taghrīq. The findings indicate that taghrīq is a regulated judicial tool applied when injustice is proven, ownership cannot be determined, and scholarly authorization is obtained. Historically, it enabled redistribution of illicit wealth for public welfare, forming a sophisticated Ibāḍī framework for financial accountability.